Milne-type inequalities for third differentiable and h-convex functions - Benaissa, Bouharket; Budak, Hüseyin (Boundary value problems, 2025)
This paper develops a novel Milne inequality for third-differentiable and h -convex functions using Riemann integrals. Furthermore, new Milne inequalities are proposed utilizing a summation parameter p ≥ 1 for s -convexity, convexity, and P -functions class. We examine cases when the third derivative functions are also bounded and Lipschitzian.